2018
DOI: 10.1039/c8ta05068f
|View full text |Cite
|
Sign up to set email alerts
|

Na-ion battery cathode materials prepared by electrochemical ion exchange from alumina-coated Li1+xMn0.54Co0.13Ni0.1+yO2

Abstract: Electrochemical ion exchange in a sodium cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Many attempts have been made recently to synthesize cathode materials with desired structures and properties by means of electrochemical ion exchange or by molten salt ion exchange. A representative example of the electrochemical Li/Na exchange is olivine-type Na x Li 1– x FePO 4 (space group Pnma , 0 ≤ x ≤ 1) . Through conventional chemical methods under high temperature or a hydrothermal environment, maricite-type NaFePO 4 ( Pnma ) with poor electrochemical activity (no Na + channels) is always formed because it is thermodynamically favored .…”
Section: Introductionmentioning
confidence: 99%
“…Many attempts have been made recently to synthesize cathode materials with desired structures and properties by means of electrochemical ion exchange or by molten salt ion exchange. A representative example of the electrochemical Li/Na exchange is olivine-type Na x Li 1– x FePO 4 (space group Pnma , 0 ≤ x ≤ 1) . Through conventional chemical methods under high temperature or a hydrothermal environment, maricite-type NaFePO 4 ( Pnma ) with poor electrochemical activity (no Na + channels) is always formed because it is thermodynamically favored .…”
Section: Introductionmentioning
confidence: 99%
“…[ 23–25 ] Heat treatment with inorganic materials or carbo‐thermal reduction has also been carried out for achieving improved redox kinetics and superior electrochemical cycling behavior. [ 26,27 ] One of the promising approaches is surface coatings using metal oxides like TiO 2 , [ 28 ] ZrO 2 , [ 29 ] Al 2 O 3 , [ 28,30,31 ] and Li‐ion conducting materials, for instance, lithium aluminate, [ 32–35 ] lithium zirconate, [ 29 ] sodium aluminate. [ 36,37 ] These coatings effectively lessen the undesired detrimental surface reactions of solutions species and HE‐NCM cathodes, diminishing thus TMs dissolution upon prolonged cycling.…”
Section: Introductionmentioning
confidence: 99%
“…[ 38,39 ] Alumina (Al 2 O 3 ) coated Li and Mn‐rich cathode materials showed altered surface morphologies with improved electrochemical results. [ 28,30,31 ] In contrast, the lithium aluminate coatings on these materials bring out the synergistic effect of surface protection due to high chemical stability and faster Li‐ion transport kinetics by reducing the cell impedance upon cycling. [ 32–35 ] The positive impact of sodium aluminate coating on layered cathode materials like LiCoO 2 [ 36 ] or Ni‐rich material (NCM523) [ 37 ] has also been studied where the formation of 2D ion diffusion channels [ 40 ] upon charging has been accounted for the superior electrochemical performances.…”
Section: Introductionmentioning
confidence: 99%
“…erefore, sodiation in delithiated host with the lowest remained lithium-ions is another way to enhance the electrochemical properties of the sodium cathode. Recent studies have reported the use of a delithiated cathode phase as a sodium intercalation host for Na-ion batteries, including layered oxide, phosphates, and Li-rich cathodes [13,[17][18][19][20]. Previously, we studied the full sodiation into LiNMC synthesized via sol-gel reaction [13].…”
Section: Introductionmentioning
confidence: 99%